Understanding the diversity of farming systems and assessing the profitability of farming activities of beneficiaries of the Zimbabwe land reform programme : the case of Chegutu district (Ward 12) - Anseeuw, Ward, 1974- (University of Pretoria, 2016)
Dissertation (MSc)--University of Pretoria, 2016.